Management of Monosymptomatic Nocturnal Enuresis in Children: A Pilot Randomised Control Trial of Body‐Worn Versus Bell‐and‐Pad Alarm Device - Blake Peck; Daniel Terry; Bronwyn Peck; Andrea Green; Kerrie Svedas; Shirley Whitaker; Monica Harrop; Erica Pearce; Mark Nethercote; Natasha Burgess; Ha N. D. Le; Sithara Wanni Arachchige Dona; et al. (Journal of Paediatrics and Child Health, 2026)
ABSTRACT Aim To compare bell‐and‐pad alarm therapy to body‐worn alarm therapy for the management of monosymptomatic enuresis in children 6–16 years of age in Victoria, Australia. Method A sample of 76 children with monosymptomatic enuresis were randomly allocated to a control group (bell‐and‐pad alarm, n = 38) or an experimental group (body‐worn alarm, n = 38). All children were treated for 8 weeks. Children who had not been successful, defined as 14 consecutive dry nights, continued therapy up to 16 weeks. The two alarm types were compared using dichotomous cross‐tabulations and chi‐squared tests of independence based on the most positive outcome versus the other outcomes. The costs of the treatment were calculated from the service provider's and family's perspective. Costs were in 2023 Australian dollars. Results Treatment success was achieved in 22 children (68.7%) in the body‐worn alarm group and 34 children (94.4%) in the routine (bell‐and‐pad) group ( p = 0.010). The bell‐and‐pad alarm also performed better on three other indicators: Alarm used every night ( p = 0.018), alarm woke parent ( p = 0.011), and child was compliant with alarm use ( p = 0.015). The body‐worn treatment was found to be cheaper than the bell‐and‐pad treatment ($598 per child) but was not as effective. Conclusion The success rates for treatment were high in both groups but the bell‐and‐pad alarm was found to be more effective than the body‐worn alarm used in this study. Further research is recommended, with a larger population, to establish more definitive support for clinical decision making. Trial Registration: Australian and New Zealand Clinical Trials Registry ACTRN12619000354189